2021
DOI: 10.3390/su132111873
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Optimization Considering Sustainability Aspects

Abstract: Supply chain optimization concerns the improvement of the performance and efficiency of the manufacturing and distribution supply chain by making the best use of resources. In the context of supply chain optimization, scheduling has always been a challenging task for experts, especially when considering a distributed manufacturing system (DMS). The present study aims to tackle the supply chain scheduling problem in a DMS while considering two essential sustainability aspects, namely environmental and economic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In the economic and quality field, binary linear-programming optimization by minimization of the cost, while optimizing environmental pollution and the quality of products, was proposed by [22,23]. Moreover, in the electrical field, integer linear programming was used to maintain energy storage and prolong the battery life cycle, while minimizing load shedding [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the economic and quality field, binary linear-programming optimization by minimization of the cost, while optimizing environmental pollution and the quality of products, was proposed by [22,23]. Moreover, in the electrical field, integer linear programming was used to maintain energy storage and prolong the battery life cycle, while minimizing load shedding [24].…”
Section: Discussionmentioning
confidence: 99%
“…From the analysis of recent works, it is observed that the emphasis is on the product [17][18][19][20][21][22][23][24][25] and not on the organization. Thus, to eliminate all the shortcomings mentioned above, a multi-criterial optimization was conceived, focusing on economic, environmental, and social development.…”
Section: Discussionmentioning
confidence: 99%
“…After presenting the mathematical model of the problem, they proposed a possibilistic model and a robust possibilistic model to consider the uncertainty in the problem. Bank et al 24 integrated production and distribution scheduling problems with lot‐sizing decisions to minimize total sequence‐dependent setup costs, holding costs, delivery costs, and delay penalties. After presenting two mathematical models for the problem, they proposed a hybrid GA to solve the problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…LaRoche-Boisvert et al 26 investigated the integration of mine-to-port transportation into production planning and proposed a long-term stochastic integer programming model to optimize multiple objective functions, including production scheduling costs at the mines, stockpile reclamation costs, the equipment fixed cost, mining and mine-to-port transportation costs, and the risks related to meeting product demand at the port. Beheshtinia et al 27 studied integrated production and scheduling problem in a supply chain considering distributed manufacturing system. They developed a new GA named GA-TOPKOR to minimize the total orders' delivery time, transportation and production costs, and pollution level, and maximize the quality of completed orders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At present, a large number of scholars have carried out studies on supply chain, such as Beheshtinia et al An improved genetic algorithm, GA-Topkor, was proposed to solve the supply chain scheduling problem in DMS in consideration of the environment and economy in order to optimize the supply chain [4]. In terms of supply chain performance, Park focuses on the new supply chain management based on block chain and its sustainability performance in environmental protection, social equity, governance efficiency and other aspects.…”
Section: Introductionmentioning
confidence: 99%